Elastic structures - Honorato T., Matías (Universidad de Chile. Facultad de Arquitectura y Urbanismo, 2007)
The starting point for the design of this environment is a structure able to house and to promote the occupation of the space by some determined artistic communities from Berlin. This infrastructure suggests forms of actual occupation and flows that not necessarily relates to a definition by surfaces. By opposition the linear structures are disposed in a way they can promote certain degrees of use and scale. This allows shifting the notion of artistic creation from the «sponsoring institution» to a rather more spontaneous alternative. This relatively ambiguous space is thought as a series of simultaneous events and its design precedes its visible structure. In other words, what is activated through the means ofthermodynamic simulations is the programmatic gradients. This «map» ultimately conditions and defines the assembly of these divergent and converging pieces by expanding and contracting, twisting and bending themselves due their local reactions.